Avoiding the political in transition: A micro-analysis of the micro-politics of conflict. (April 2017) - Dilley, Luke T.M.
Abstract: A prominent motif that has emerged from studies focusing on the Transition Towns movement has been the movement's apolitical status and its commitment to consensus-based approaches. This apolitical stance and adherence to consensus has led some scholars to conclude that the Transition movement is an exemplar of post-political approaches to environmental problems. Despite this commitment to non-antagonistic approaches, previous studies have pointed to the emergence of conflict within and around Transition, an emergence of conflict that, some have suggested, could represent a point of departure towards a more 'political' approach. Following a semi-longitudinal research design and focusing on a particular group of Transitioners located in a rural area of the United Kingdom, this paper examines the micro-politics of conflict within this group, and shows that initially the group was able to modulate, displace and negotiate disagreement and antagonism. Overtime, however, conflict came increasingly to the fore and as this paper shows, conflict contributed to momentary articulations of the social as a sphere of inherent antagonism, contingency and power – the political proper. Yet, from these points of political potentiality, conflict did not lead to a sustained political approach, rather the group disintegrated and the post-political was re-entrenched. This paper ends by briefly reflecting on this re-entrenchment of the post-political and raises questions in relation to the effectiveness of the movement. Highlights: Semi-longitudinal research focused on a Transition Town in the United Kingdom. Examines the micro-politics of conflict within the group. Initially conflict is moderated, displaced and negated. Conflict lead to a re-entrenchment of the apolitical rather than politicization. Reflects on the effectiveness of the Transition movement.